2021
DOI: 10.1016/j.polymdegradstab.2020.109453
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical analysis of a silane-grafted polyethylene stabilised with an excess of Irganox 1076®. Proposal of a microstructural model

Abstract: chemical analysis of a silane-grafted polyethylene stabilised with an excess of Irganox 1076®. Proposal of a microstructural model -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 26 publications
3
11
0
Order By: Relevance
“…13 ), there is no longer melting peak of AO crystals on the DSC thermograms. This result is not surprising because, in our previous study [33] , it was shown that AO crystals are only present at the sample surface.…”
Section: Morphological Changes (Dsc Analysis)supporting
confidence: 58%
See 3 more Smart Citations
“…13 ), there is no longer melting peak of AO crystals on the DSC thermograms. This result is not surprising because, in our previous study [33] , it was shown that AO crystals are only present at the sample surface.…”
Section: Morphological Changes (Dsc Analysis)supporting
confidence: 58%
“…These concentrations were estimated using Eq. 2 and the calibration curve obtained for OIT at 205 °C in our previous work [33] .…”
Section: Surface Analysis (Ftir Spectroscopy In Atr Mode Vs Optical M...mentioning
confidence: 96%
See 2 more Smart Citations
“…Low-weight (molecular) antioxidants are prone to blooming, as their diffusion coefficient within the polymer is higher [9]. In a recent paper, Xu et al [10,11] studied the blooming of the molecular phenolic antioxidant Irganox 1076® at the surface of silane-crosslinked polyethylene.…”
Section: Introductionmentioning
confidence: 99%